THE NARRATORS OF THE WORK "FUTUH AL-BULDAN" AND THEIR SPECIFIC ASPECTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article mentions the sources of the work "Futuh al-bulldan" by the historian Ahmad ibn Yahya al-Balozuri, who lived in the 9th century. During the time the author lived, it was widespread to narrate historical events by verbally. Thus, most of the sources of the work shape the narrative from al-Balozuri's teachers. In some places, you can also find the narration of people who took part in the historical event. Although the author does not mention in the work that he used written sources from his method of presenting information, one can recognize that he also used historical works.